THE STABILITY OF HYDROUS POTASSIC PHASES IN LHERZOLITIC MANTLE-AN EXPERIMENTAL STUDY TO 9.5 GPA IN SIMPLIFIED AND NATURAL BULK COMPOSITIONS - Konzett J.; Ulmer P. (My University, 1999)
To investigate the pressure stability limit of phlogopite and the pressure–temperature stability field of its breakdown product K-richterite, experiments were conducted from 4.0 to 9.5 GPa and between 800°C and 1400°C in a subalkaline system K 2 o–Na 2 O–CaO–MgO–Al 2 O 3 –SiO 2 –H 2 O (KNCMASH) and in natural phlogopite and K-richterite-doped lherzolite systems. In KNCMASH, phlogopite breaks down between 6.0 and 6.5 GPa at 800°C and between 6.5 and 7.0 GPa at 1100°C to form potassic amphibole by the reaction phlogopite + clinopyroxene + orthopyroxene = K-richterite + garnet + olivine + H 2 O. In the natural system, the stability field of amphibole is shifted towards lower pressures by ∼0.5 GPa. The high-temperature stability limit of K-richterite in KNCMASH was located between 1300 and 1400°C at 8.0 GPa and at <1300°C at 7.0 GPa. Thus, K-richterite can be stable in the mantle wedge above subduction zones below a depth of ~180–200 km. Because of the small difference in K/OH ratios between phlogopite and K-richterite, only a small amount of aqueous fluid is likely to be produced during phlogopite breakdown in an average mantle lherzolite bulk composition. This fluid might be trapped by nominally anhydrous minerals before it can migrate to hotter portions of the mantle wedge. Phlogopite breakdowntherefore is unlikely to be a factor in inducing significant melting of the wedge leading to arc magmatism.